Dante’s Pluralism and the Islamic Philosophy of Religion - Stone, G. author. aut Link
VII, 326 p.
Keywords: This book explores the Islamic roots of the Western values of tolerance and religious pluralism, and considers Dante from the perspective of the Arab-Islamic philosophical tradition. It examines the relations between Islamic and Western thought, the historical origins of Western values, and the tradition of tolerance in classical Islamic thought.